MOF‐Mediated Synthesis of Supported Fe‐Doped Pd Nanoparticles under Mild Conditions for Magnetically Recoverable Catalysis. Issue 60 (5th October 2020) - Darawsheh, Mohanad D.; Mazarío, Jaime; Lopes, Christian W.; Giménez‐Marqués, Mónica; Domine, Marcelo E.; Meira, Debora M.; Martínez, Jordan; Mínguez Espallargas, Guillermo; Oña‐Burgos, Pascual
Abstract: Metal–organic framework (MOF)‐driven synthesis is considered as a promising alternative for the development of new catalytic materials with well‐designed active sites. This synthetic approach is used here to gradually transform a new bimetallic MOF, with Pd and Fe as the metal components, by the in situ generation of aniline under mild conditions. This methodology results in a compositionally homogeneous nanocomposite formed by Fe‐doped Pd nanoparticles that, in turn, are supported on iron oxide‐doped carbon. The nanocomposite has been fully characterized by several techniques such as IR and Raman spectroscopy, TEM, XPS, and XAS. The performance of this nanocomposite as an heterogeneous catalyst for hydrogenation of nitroarenes and nitrobenzene coupling with benzaldehyde has been evaluated, proving it to be an efficient and reusable catalyst. Abstract : Nanocomposites based on Fe‐doped Pd nanoparticles supported on iron oxide‐doped carbon have been obtained from a bimetallic PdFe‐MOF. Controlled decomposition of the PdFe‐MOF upon in situ generation of aniline leads to ultra‐small, homogeneous PdFe‐NPs. The PdFe‐NPs are better catalysts of the hydrogenation of nitroarenes than commercial Pd@C and offer the possibility of being magnetically recovered.